(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
El Nino episodes are major climatic disruptions that occur every 2 to 8 years and originate in the equatorial Pacific Ocean. From the coastlines of Peru and Ecuador to the middle of the equatorial Pacific Ocean, unusually warm waters at the ocean surface mark the developed phase of El Nino. The reason of this occurrence is a peculiar lessening of the westward blowing trade winds, which enables warm surface waters to reverse their course eastward. El Nino’s climatic effects are increasing throughout the globe, and this may have a variety of consequences on regional weather. It is linked to a broad range of changes in the climate system, and it has the potential to have significant socio-economic consequences in the infrastructure, agricultural, health, and energy sectors. Despite the fact that El Nino occurs in the tropical Pacific, it has an effect on worldwide climate and weather events such as drought, floods, and tropical storms. The usual state in the equatorial Pacific has altered because of increased greenhouse gas emissions, which has resulted in changes in the El Nino Southern Oscillation (ENSO). ENSO fluctuations will continue to exist and affect global climate conditions in the future decades and millennia, we can be certain. As a result, both scientists and the public rely on predicting and understanding ENSO conditions. The occurrence of El Nino and its effect on world climate and socio-economic status have been researched and discussed in this article.